Comparative effects of nitric oxide and salicylic acid on salinity tolerance in saffron (Crocus sativus). (2nd January 2021) - Babaei, Samareh; Niknam, Vahid; Behmanesh, Mehrdad
Abstract: Salinity is a major environmental stress worldwide that adversely affects plant's growth and metabolism. Various studies have demonstrated the positive effect of growth regulators on improving stress tolerance of plants. In this study, Crocus sativus as a profitable herb and expensive spice was subjected to nitric oxide and salicylic acid treatments to improve its sustainability under salinity stress. Based on our results treating Crocus sativus corms with nitric oxide caused more growth under salinity stress, also nitric oxide was able to reduce stress effects by compatible solutes accumulation, inducing antioxidative enzyme activities and increasing the biosynthesis of secondary metabolites. However, salicylic acid treatment did not improve plant growth under salinity.